Personality disorder: complex cases or difficult cases?: a question of placement in forensic services - Harrison, Antonia C. (2015)
This thesis explored whether patients in high security hospitals are more ‘Complex Cases’ or more ‘Difficult Cases’ than their counterparts in lower security settings. Herein, case complexity is associated with co-morbid diagnoses or clinical needs, whilst case difficulty refers to challenging, violent and aggressive behaviour.